Penentuan Titik IGS sebagai Titik Ikat dalam Pengolahan Data GNSS untuk Studi Geodinamika di Pulau Sumatra - Satrio Muhammad Alif; Pungkas Tri Hapsoro (Jurnal Tekno Global, 2021)
Geodynamic studies on the Sumatra island generally use GNSS data. GNSS data processing using the differential method by using the IGS point as a tie point. This study aims to determine good IGS point in processing GNSS data for geodynamic studies on the Sumatra island. The data used are GNSS data from 3 SuGAr points and 20 IGS points in 2019 with DOY 061, 062, and 063. 211 GNSS data processing is carried out using different IGS points. The number of tie points used are 18, 19, and 20 IGS points. Determination of a good IGS point is based on the results of the standard deviation. The factors that cause the standard deviation value are the quality of the IGS point, distance, and temperature value. The processing results with 18 IGS points are better than 20 IGS points when using poor IGS points. The processing quality at the SuGAr point on the southern part of Sumatra Island (TJKG point) is the best compared to the other two SuGAr points. IGS points that are bad for geodynamic studies are XMIS and PBRI points because of the high standard deviation values for close distances. Good IGS points with low standard deviation values are COCO, DGAR, and LHAZ points. The low temperature value at the LHAZ point is thought to be the cause of the low standard deviation value.  Keywords : GNSS, Standard Deviation, Precision, IGS, Differential